Transformasi Musik Pada Ritual Tradisi Kebangru’an: Kajian Sosiologi Seni - Yuga Anggana Sosani (UIN Mataram, 2021)
This paper discusses the role of artists in society as things that influence the creative process of artists in transforming works of art in the Kebangru'an ritual, as well as the form of presentation, functions and values that are ​​contained in Kebangru'an Music. The method of this research uses a qualitative research paradigm with a sociology of art study approach to find out how the role of artists in society as a matter of influencing the creative process of artists in transforming works of art in the Kebangru'an ritual, as well as the form of presentation, functions and values that are ​​contained in Kebangru'an Music. The data was collected by means of observation and in-depth interviews. The observations are carried out by observing various actions that are patterned and reflected the thinking system of the Kebangru'an Music artist which includes speech, expression, statement, outlook on life, and his life history. The result of the study shows that the social status of artists as civil servants and community leaders is a factor that affects the work of artists, the role of artists in society is also a factor in changing the paradigm of society towards Kebangru'an Music. Kebangru'an music is presented with the addition of song texts that function as a means of communicating advice, moral messages in life, also a media that strengthen conformity to social norms. Kebangruan music has values ​​of worship and tolerance or community harmony.